2011
DOI: 10.1210/en.2011-1106
|View full text |Cite
|
Sign up to set email alerts
|

Male Hypogonadism and Germ Cell Loss Caused by a Mutation in Polo-Like Kinase 4

Abstract: The genetic etiologies of male infertility remain largely unknown. To identify genes potentially involved in spermatogenesis and male infertility, we performed genome-wide mutagenesis in mice with N-ethyl-N-nitrosourea and identified a line with dominant hypogonadism and patchy germ cell loss. Genomic mapping and DNA sequence analysis identified a novel heterozygous missense mutation in the kinase domain of Polo-like kinase 4 (Plk4), altering an isoleucine to asparagine at residue 242 (I242N). Genetic compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Thirteen genes were known to be required for the development of male germ cells (Vps54, Mdm2, Agfg1, Plk4, Ppp1cc, Bcl2l2, Cep55, Ccny, Hnrnpl, Etv5, Cdc7, Dicer1 and Ezh2) ( Table 1) (Kang-Decker et al, 2001;Kim et al, 2003;Yan et al, 2003;Schmitt-John et al, 2005;Liu et al, 2007;Tyagi et al, 2009;Chang et al, 2010;Harris et al, 2011;Korhonen et al, 2011;Lambrot et al, 2012;Li et al, 2012;Mikolcevic et al, 2012;Sinha et al, 2013) In addition, a number of the downregulated genes had been previously shown to induce apoptosis when deleted (Hnrnpl, Klf4, Ebf3, Map4k4, Zbtb18, Fbxo45, Setd8, Bcl2l2, Rrm2b, Cfdp1, Ugcg, Fut8, Ptpn11 Rpl23, Etv5, Atf2, Cul1, Tomm70a, Cdc7, and Dicer1) ( Table 2) (Diekwisch and Luan, 2002;Kim et al, 2003;Yan et al, 2003;Zhao et al, 2006;Devlin et al, 2008;Peschiaroli et al, 2009;Tyagi et al, 2009;Wang et al, 2009;Cai et al, 2011;Korhonen et al, 2011;Liu et al, 2011;Takano et al, 2011;Baubet et al, 2012;Driskell et al, 2012;Haynes et al, 2012;Li et al, 2012;Wu et al, 2012;Chen et al, 2013;El-Karim et al, 2013;Peng et al, 2013;Walluscheck et al, 2013). Further, we compared the genes having functions spermatogenesis or apoptosis with the 117 genes showing the expression pattern decreasing from spermatocyte to spermatid (Fig.…”
Section: Genes Downstream Of Zfp819mentioning
confidence: 99%
“…Thirteen genes were known to be required for the development of male germ cells (Vps54, Mdm2, Agfg1, Plk4, Ppp1cc, Bcl2l2, Cep55, Ccny, Hnrnpl, Etv5, Cdc7, Dicer1 and Ezh2) ( Table 1) (Kang-Decker et al, 2001;Kim et al, 2003;Yan et al, 2003;Schmitt-John et al, 2005;Liu et al, 2007;Tyagi et al, 2009;Chang et al, 2010;Harris et al, 2011;Korhonen et al, 2011;Lambrot et al, 2012;Li et al, 2012;Mikolcevic et al, 2012;Sinha et al, 2013) In addition, a number of the downregulated genes had been previously shown to induce apoptosis when deleted (Hnrnpl, Klf4, Ebf3, Map4k4, Zbtb18, Fbxo45, Setd8, Bcl2l2, Rrm2b, Cfdp1, Ugcg, Fut8, Ptpn11 Rpl23, Etv5, Atf2, Cul1, Tomm70a, Cdc7, and Dicer1) ( Table 2) (Diekwisch and Luan, 2002;Kim et al, 2003;Yan et al, 2003;Zhao et al, 2006;Devlin et al, 2008;Peschiaroli et al, 2009;Tyagi et al, 2009;Wang et al, 2009;Cai et al, 2011;Korhonen et al, 2011;Liu et al, 2011;Takano et al, 2011;Baubet et al, 2012;Driskell et al, 2012;Haynes et al, 2012;Li et al, 2012;Wu et al, 2012;Chen et al, 2013;El-Karim et al, 2013;Peng et al, 2013;Walluscheck et al, 2013). Further, we compared the genes having functions spermatogenesis or apoptosis with the 117 genes showing the expression pattern decreasing from spermatocyte to spermatid (Fig.…”
Section: Genes Downstream Of Zfp819mentioning
confidence: 99%
“…Moreover homozygous deletions of Plk2 or Plk3 do not result in fertility defects in mice (Ma et al, 2003;Myer et al, 2011). Like Plk1, Plk4 is essential for cell viability and its meiotic role has not been definitively tested, although when heterozygous, an ENU-induced Plk4 mutation within the kinase domain (Plk4 m1Lja ) causes a testicular phenotype of focal regions of germ-cell loss (Harris et al, 2011), but not meiotic arrest or infertility. Our finding that PLK4 is sequestered to the X-Y body during pachynema and diplonema could implicate a role in meiotic sex chromosome inactivation (Royo et al, 2010).…”
Section: Plk1 the Sc And Desynapsismentioning
confidence: 99%
“…[19][20][21] Hence, our current study patient likely survived due to the residual marginal activity of PLK4. We speculate that the reduced activity of the p.(M148V) variant rather than a loss-of-function prevented embryonic lethality.…”
Section: Discussionmentioning
confidence: 85%